2018
DOI: 10.1098/rsos.171858
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale investigation of the formation and properties of high-grade rutile TiO 2 from titanium slags using microwave heating

Abstract: In this paper, the phase transition of titanium slag under microwave heating observed through electron microscopy was systematically investigated. The phase identification and transformation as well as the morphology of samples before and after each treatment were characterized using X-ray powder diffraction (XRD), Fourier-transform infrared spectroscopy, Raman spectroscopy and scanning electron microscopy (SEM). The XRD confirmed that sodium salt roasting could modify the phase composition of titanium slag. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In addition, the two bands observed at 968 and 630 cm –1 are due to VO and δ-OPO vibrations, respectively. ,, In the spectrum of TiO 2 , OH stretching and bending vibrations are observed at 3434 and 1638 cm –1 , belonging to the surface OH groups and adsorbed water molecules. The broad peak appearing at 470–550 cm –1 was attributed to the stretching vibration of the Ti–O–Ti bonds. In the spectrum of VPO­(30 wt %)@TiO 2 , the broad peak in the range of 450–600 cm –1 is assigned to the stretching vibrational mode of the Ti–O–Ti bonds at TiO 2 matrix in VPO­(30 wt %)@TiO 2 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the two bands observed at 968 and 630 cm –1 are due to VO and δ-OPO vibrations, respectively. ,, In the spectrum of TiO 2 , OH stretching and bending vibrations are observed at 3434 and 1638 cm –1 , belonging to the surface OH groups and adsorbed water molecules. The broad peak appearing at 470–550 cm –1 was attributed to the stretching vibration of the Ti–O–Ti bonds. In the spectrum of VPO­(30 wt %)@TiO 2 , the broad peak in the range of 450–600 cm –1 is assigned to the stretching vibrational mode of the Ti–O–Ti bonds at TiO 2 matrix in VPO­(30 wt %)@TiO 2 …”
Section: Resultsmentioning
confidence: 99%
“…The formation of Fe2O3/TiO2 mixed oxides was further confirmed by Fourier transform infrared attenuated total reflection (FT-IR ATR) spectroscopy as shown in Figure 2a. In the FT-IR ATR spectra of Fe2O3/TiO2 composite, the adsorption bands at 1082.38 cm −1 and 464.05 cm −1 are ascribed to the bending vibrations of O-H and stretching vibrations of metal-O (Ti-O, Fe-O) [33], respectively. The above results indicated that Fe2O3/TiO2 composites were successfully fabricated from titanium slag.…”
Section: Characterizationmentioning
confidence: 99%
“…Recently, Chen et.al. introduced a novel process with five steps including hydrochloric acid leaching for the synthesis of rutile TiO 2 from titanium slags, which utilized a microwave sodium salt (Na 2 CO 3 ) roasting to improve the leaching efficiency [19] . Microwave irradiation technology is known to be superior to the use of conventional heating on accelerating reaction rates, improving yields, and selectively activating or suppressing reaction pathways [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%